Comparison of Staphylococcal cassette chromosome mectypes and antimicrobial susceptibility patterns of Staphylococcus aureus isolated from clinical samples in Lebanon. (c2007) - Jabbour, Dina (2007)
Bibliography: leaves. 83-93.